Studies on the Effect of Ageing on Thermal, Ballistic and Mechanical Properties of Advanced Energetic Propellants. Issue 4 (15th February 2021) - Kumar, Amit; Sadavarte, Vaibhav S.; Santosh Mada, S. S. N. M.; Pande, Shrikant M; Chavan, Prakash V.
Abstract: In order to study the ageing behaviour of advanced energetic propellants during storage and the effect of nitrate ester on the shelf life, accelerated ageing tests were conducted on two types of propellants based on nitrate esters, BTTN (as P‐1) and NG:BTTN (1 : 1) mixture (as P‐2). Mechanical and ballistic characterization of P‐1 and P‐2 propellants were carried out during storage at ambient (27 °C) and elevated temperature (40 °C and 55 °C). During ageing, tensile strength and Young's modulus of propellants are increasing and percentage elongation is decreasing due to depletion of nitrate ester from the locus. Also, there is a loss of stabilizer with time during ageing. Thermal decompositions of P‐1 and P‐2 were studied using differential thermal analysis at four heating rates (1 °C/min, 2 °C/min, 5 °C/min, and 10 °C/min) during ambient and accelerated ageing. Activation energies for thermal decomposition were calculated using Kissinger's and Ozawa's methods by assuming first‐order reaction kinetics for first stage decomposition in DSC studies of aged propellants. The shelf life of propellants was predicted based on the classical Arrhenius equation using zero‐order kinetics of degradation of the propellant mechanical property i. e. percentage elongation. With the 30 percentage elongation as the critical evaluation parameter, predicted shelf life at 25 °C is 23.97 years and 12.17 years for P‐1 and P‐2 respectively. Abstract :